Effect of a change in selection year on success in male soccer players - Helsen, W. F.; Starkes, J. L.; van Winckel, J. (American Journal of Human Biology, 2001)
Since 1997 and following the guidelines of the International Football Association, the Belgian Soccer Federation has used January 1st as the start of the selection year. Previously, August 1 was the start. This shift prompted an investigation of changes in birth-date distributions throughout youth categories for 1996-1997 compared to the 1997-1998 competitive years. Birth dates were considered for national youth league players, ages 10-12, 12-14, 14-16, and 16-18 years. Kolmogorov Smirnov tests assessed differences between observed and expected birth-date distributions. Regression analyses examined the relationship between month of birth and number of participants both before and after the August to January shift. Results indicated that from 1996 to 1997, youth players born from January to March (the early part of the new selection year) were more likely to be identified as "talented" and to be exposed to higher levels of coaching. In comparison, players born late in the new selection year (August to October) were assessed as "talented" in significantly lower proportions. Specific suggestions are presented to reduce the relative age effect.